(untitled) (PIONIR: JURNAL PENDIDIKAN, 2020)
The PPL management unit at the LPTK is very important to make student teacher candidates competent. Students as prospective educators must have teacher competence, in the form of abilities and skills in managing learning properly. These abilities and skills are shown by the ability to plan lessons, carry out learning and evaluate learning. The reality is that the teacher competence of PPL students is still not optimal, such as PPL students who have not used various methods, have not implemented the learning process using a scientific approach, in addition, there are still students who are not disciplined. This study uses a qualitative approach that seeks to interpret the phenomena experienced by research subjects. The research method used is descriptive analysis method. The results showed that the teaching competence of PPL students (academic and non-academic) was generally good. It only needs strengthening in the field of developing varied learning models, strengthening social competence and self-confidence. Furthermore, there are two factors that affect student competence in school, namely internal and external factors. Then the role of the PPL unit has also been good, the process has been carried out since the preparation then continued with implementation, evaluation and follow-up. However, it is necessary to increase coordination between the PPL unit and schools, especially regarding the initial PPL preparation.